Kulturtourismus für alle?: Neue Strategien für einen Wachstumsmarkt - Schmidt-Ott, Thomas; Pröbstle, Yvonne; Klein, Armin (transcript, 2017)
Cultural tourism is changing. With services that set themselves apart from the classic cultural sector, tourist operators are trying to respond to the evolving needs of travellers. But does this actually succeed in reaching groups of people beyond the traditional cultural public? And is there any prospect of them being transferred back into the cultural sector? This volume focuses on the manifestations of cultural tourism that have until now been neglected in discussions on the subject, and which evade typical classification into categories and institutions. An enlightening contribution to the debate on the challenges of cultural tourism.